2020
DOI: 10.1002/csc2.20366
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forage nutritive value of reduced‐lignin alfalfa during regrowth

Abstract: Genetically engineered alfalfa (Medicago sativa L.) cultivars with reduced lignin (RL) concentration are commercially available but their change in nutritive value as the crop matures within a growth cycle has not been thoroughly documented and might differ from non-RL cultivars. This research documents changes in forage nutritive value of a RL cultivar (HarvXtra-008) and two non-RL cultivars (54R02 and WL355RR) within five growth cycles across 2 yr in six states in the United States. A randomized complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Grev et al [ 9 ] also reported that CP concentrations of reduced lignin alfalfa (54HVX41) were not significantly different to CP concentrations of other varieties at two of three locations in both seeding year and first production year. The improved traits of new varieties showed certain degree of advantages in CP levels [ 4 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Grev et al [ 9 ] also reported that CP concentrations of reduced lignin alfalfa (54HVX41) were not significantly different to CP concentrations of other varieties at two of three locations in both seeding year and first production year. The improved traits of new varieties showed certain degree of advantages in CP levels [ 4 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported a 20 to 30% alfalfa yield increase compared 3-cut to 4-cut in a season involving the new reduced lignin variety [ 6 ]. Two studies including reduced and low-lignin varieties also found benefits of reducing the number of cuts per season [ 4 , 9 ]. There are limited data on the performance of the new variety in the first and second production year, under a fixed harvest frequency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we chose d 30 of chronological age for this project, and second cutting to avoid harvest of any fall growth, to lessen the risk of grass growth in the sward, and to assure uniformity of plant re-growth initiation. Across a wide variety of alfalfa cultivars, ADL concentration is less at a 30-d, rather than 40-d, cutting interval ( Sulc et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%